Perataan Laba terhadap Reaksi Pasar dengan Mekanisme GCG dan CSR Disclosure - Restuningdiah, Nurika (Universitas Prasetiya Mulya, 2010)
The purpose of this research is to examine the impact of income smoothing to the market reaction with the good corporate governance mechanism and corporate social Responsibility disclosure as a moderating variable. The proxy of good corporate governance mechanism are institutional ownership, managerial ownership, independency of board commisioner and the size of board commisioner. Regression analysis of 30 public companies listed in Indonesia Stock Exchange on year 2008 until 2009 through a purposive random sampling technique indicated that income smoothing has negative effect to the market reaction. This study shows that good corporate governance mechanism is not the moderating variables to the relationship between income smoothing and the market reaction. The study also shows that corporate social responsibility disclosure is not moderating variables to the relationship between income smoothing and the market reaction, but as independent predictor for market reaction.